Responsibility Accounting, Target Costing And Business Performance: The Role Of Risk Management As Mediator - Afifa, Malik Muneer Mahmoud Abu (2018)
The crises that affected Jordanian business environment were a wake-up call for its financial institutions sparking concern on the issues of risk and performance. In Jordan, various instructions and circulars have been issued by the Central Bank of Jordan as part of the government‘s initiative to ensure good control and performance, causing the financial institutions to give more serious attention towards their management accounting and risk management practices. The present study focuses on two prominent management accounting practices i.e. responsibility accounting and target costing.